Acylglycine Analysis by Ultra‐Performance Liquid Chromatography‐Tandem Mass Spectrometry (UPLC‐MS/MS). (13th February 2018) - Hobert, Judith A.; Liu, Aiping; Pasquali, Marzia
Abstract: Quantitative analysis of urine acylglycines has shown to be a highly sensitive and specific method with proven clinical utility for the diagnosis of several inherited metabolic disorders including: medium chain acyl‐CoA dehydrogenase deficiency, multiple acyl‐CoA dehydrogenase deficiency, short chain acyl‐CoA dehydrogenase deficiency, 3‐methylcrotonyl‐CoA carboxylase deficiency, 2‐methylbutyryl‐CoA dehydrogenase deficiency, isovaleric acidemia, propionic academia, and isobutyryl‐CoA dehydrogenase deficiency. Here, a method that is currently performed using ultra‐performance liquid chromatography/tandem mass spectrometry (UPLC‐MS/MS) is described. © 2016 by John Wiley & Sons, Inc.